Manufacturing of nanoparticle-filled PA11 composite particles for selective laser sintering - Dechet, Maximilian; Lanzl, Lydia; Wilden, Alisa; Sattes, Maria-Melanie; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Simple and Reliable Method for Studying the Adsorption Behavior of Aquivion lonomers on Carbon Black Surfaces - Damm, Cornelia; Thoma, Martin; Hoffmann, Eva-Maria; Sattes, Maria-Melanie; Segets, Doris; Peukert, Wolfgang; Lin, Wei (Langmuir, 2018)
A better understanding of the interactions of carbon black and perfluorinated sulfonic acid (PFSA) ionomer helps to improve the effectiveness of polymer electrolyte membrane fuel cells. We present a simple and fast method for quantitative PFSA ionomer analysis based on suspension density measurements. After validation of the reliability of our method by thermogravimetric analysis and isothermal titration calorimetry (ITC), we investigate the adsorption equilibrium of short-side-chain PFSA ionomers of different equivalent weights (EW) and polarities on carbon black. The measured adsorption isotherms exhibit a plateau in the ionomer surface concentration for ionomer equilibrium concentrations <= 2 g/L. In this concentration range, the adsorption isotherms are described by the Langmuir model, whereby the surface concentrations in the plateau region are between 0.041 and 0.070 g/g. The plateau value of the ionomer surface concentration increases with EW and therefore with decreasing number of side chains with terminal sulfonic acid group per ionomer molecule, while the amount of adsorbed sulfonic acid groups remains constant for all investigated ionomers, resulting in similar zeta-potentials and sedimentation stability of the suspensions. The free energies of adsorption Delta G calculated from the association constants of the adsorption isotherms agree well with Delta G values obtained by isothermal titration calorimetry (ITC) and thus validate the adsorption isotherm measurement method. From the values of adsorption enthalpy Delta H ((-7.3 +/- 0.8) kJ/mol) and entropy Delta S (ca. 100 J/(mol K)), which were extracted from ITC, we conclude that the ionomer adsorption on carbon black is a spontaneous physisorption process.
Keywords: nano; carbon; allotrope; black